Unmasking recurrent melena as the initial presentation of metastatic prostate cancer: a case report - Wang, Xiao; Wang, Lixia; Sun, Kaiqi; Gao, Ying; Wei, Lai; Duan, Zhijun (Frontiers in Oncology, 2025)
BackgroundProstate cancer, a common malignancy in the male population, is typically characterized by urinary symptoms, such as urinary obstruction and frequency. This report presents a rare case of metastatic prostate cancer that initially manifested with recurrent melena.Case presentationA 70-year-old man with recurrent melena was admitted to the hospital. Laboratory workups revealed significant pancytopenia, as well as highly elevated serum prostate-specific antigen (PSA) concentrations. However, both upper gastrointestinal endoscopy and colonoscopy found no abnormal bleeding lesions. Further positron emission tomography/computed tomography (PET/CT) examination and pathological results from the bone marrow and prostate gland confirmed the diagnosis of prostate cancer and bone metastasis. After androgen deprivation therapy (goserelin) along with an androgen receptor antagonist (darolutamide), the patient’s serum total PSA level declined drastically to 0.01ng/ml, accompanied by an improvement in pancytopenia. During follow-up, he reported significant symptomatic improvement, such as the cessation of melena.ConclusionWhen encountering male patients with recurrent melena as the initial presentation, clinicians should be vigilant about the possibility of metastatic prostate cancer. Moreover, a comprehensive evaluation based on multimodality evidence and multidisciplinary management can inform an individualized therapeutic plan for prostate cancer progression.